2013
DOI: 10.1111/jvp.12100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and ex‐vivo pharmacodynamics of cefquinome against Klebsiella pneumonia in healthy dogs

Abstract: A two-period cross-over study was carried to investigate the pharmacokinetics (PK) and ex-vivo pharmacodynamics (PD) of cefquinome when administrated intravenously (IV) and intramuscularly (IM) in seven healthy dogs at a dose of 2 mg/kg of body weight. Serum concentrations were determined by HPLC-MS/MS assay and cefquinome concentration vs. time data after IV and IM were best fit to a two-compartment open model. Cefquinome mean values of area under concentration-time curve (AUC) were 5.15 μg · h/mL for IV dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…PK/PD indices, such as C max /MIC and AUC 0–24 h /MIC values of the target organism, have been used to predict the clinical efficacy of antibacterial agents. Another important PK/PD parameter to describe drug efficacy is the time during which the drug concentration exceeds the MIC ( T > MIC) [42]. It is generally recommended that T > MIC should be at least 50% of the dosage interval to ensure an optimal bactericidal effect [42, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PK/PD indices, such as C max /MIC and AUC 0–24 h /MIC values of the target organism, have been used to predict the clinical efficacy of antibacterial agents. Another important PK/PD parameter to describe drug efficacy is the time during which the drug concentration exceeds the MIC ( T > MIC) [42]. It is generally recommended that T > MIC should be at least 50% of the dosage interval to ensure an optimal bactericidal effect [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Another important PK/PD parameter to describe drug efficacy is the time during which the drug concentration exceeds the MIC ( T > MIC) [42]. It is generally recommended that T > MIC should be at least 50% of the dosage interval to ensure an optimal bactericidal effect [42, 43]. During the present study, to optimize the marbofloxacin dosage regimen, we also calculated the T > MIC at a dose of 2.50 mg/kg of body weight in pigs after i.v., i.m., and p.o.…”
Section: Discussionmentioning
confidence: 99%
“…CFQ could potentially be used for the treatment of many turtle diseases. Pharmacokinetic studies of CFQ have been investigated in salmon (San Martín, Bataglia, Hernández, Quiroz, & Cañon, ), camels (Al‐Taher, ), rabbits (Hwang et al., ), sheep (Tohamy, ; Uney, Altan, & Elmas, ), ducks (Yuan et al., ), ponies (Smiet, Haritova, Heil, Fink‐Gremmels, & Wijnberg, ), cross‐bred wild boars (Liu et al., ), chickens (Xie, Zhang, Wang, & Du, ), pigs (Zhao et al., ), cattle (Shan et al., ), tilapia (Shan et al., ), dogs (Zhang et al., ), buffalo calves (Venkatachalam & Dumka, ), and horses (Uney et al., ). These studies have reported favorable pharmacokinetic features of CFQ, such as good absorption, high bioavailability, and primary elimination via the kidney.…”
Section: Pharmacokinetic Parameters Of Cfq In Red‐eared Sliders (N = mentioning
confidence: 99%
“…In certain cases, the use of some antibiotics resulted in a significant decrease in the K. pneumoniaenumbers; nevertheless, treatment may be re-stricted if the bacterium produces an extendedspectrum ꞵ-lactamase (ESBL). ESBLproducing K. pneumoniae, which is reluctant to different antibacterial therapies (Lautenbach et al, 2001;Zhang et al, 2014), should be medicated by an extra-lactamase-stable antibacterial.…”
Section: Introductionmentioning
confidence: 99%